Análisis de anomalías geoquímicas a partir de sedimentos fluviales para la prospección de depósitos minerales de la cuenca hidrográfica del río Gualel escala 1:50.000. - Cabrera Garrochamba, Viviana Consuelo (2018)
The study area is located within the Puyango-Catamayo hydrographic demarcation, located south of the Equator in the Province of Loja, in the cantons of Loja and Catamayo. Geologically the zone is developed by eroding a geological block of metamorphic basement Zamora series (Paleozoic age) and volcanic and volcano-clastic rocks associated with a continental volcanic arc of the Paleogene Paleogene Formation (Paleocene age) intruded by the San Lucas Batholith (60 Ma) and other intrusive bodies. The present work consisted in the zoning of areas of mining interest, by means of a statistical and spatial analysis of the variables of Hg, Au, Ag, As, Cu, Sb, Zn, Co, Mo, Ni and Pb, in the fluvial sediments of the Gualel River Hydrographic Basin, with the purpose of locating and delimiting potential areas that could be associated with mineral deposits The values of the background interval, high values and threshold value for each element were estimated. This was integrated or a 1.50 000 map sheet where they were plotted on the sampling points, the concentration ranges for each element, being able to establish the spatial variations that the elements present within the basin and in this way, using the analysis Statistical and geochemical, establish multi-elemental associations, making it possible to relate the groupings found with the geological environment present in the basin. The obtained results allowed to delimit 4 anomalous zones, for the elementary groupings analyzed. Abnormal zone 1 was related to felsic to intermediate lithologies with a high potentiality of Au-Zn-Pb. Abnormal zone 2 was associated with dioritic intrusions and andesitic lavas mainly with potential for Au-Pb-Ni elements. The anomalous zone 3 was also associated with felsic lithologies, where they present a high potential for the prospecting of mineral phases containing Au-Cu-Mo; and, anomalous zone 4 presents potential for Mo-Zn-Ni elements, associated with volcanic clastic sediments and intrusive bodies of diorite composition. Keywords: Geochemical mapping, fine sediments, geochemical prospecting, Gualel River Basin, Geochemistry-Stream Sediments, Geostatistics.